The effect of ownership structure on firm performance in Malaysia - Taufil Mohd, Kamarun Nisham; Md Rus, Rohani; Musallam, Sami R. M. (Scientific & Academic Publishing, 2013)
This paper aims to investigate and analyze the effect of ownership by different groups of investors on the performance of listed companies in Malaysia for a period of ten years from 2000 to 2009.The results of GLS show that firm performance is positive and significantly related to five government-linked investment companies, foreign ownership, and DPIIs ownership while it is negatively and significantly related to state ownership.These results imply that government ownership through GLICs does not lead to value destruction.In fact, it could lead to better monitoring.However, state ownership leads to lower values.